PENINGKATAN HASIL BELAJAR PENGUKURAN KELILING DAN LUAS BANGUN DATAR MENGGUNAKAN PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) DI KELAS V SDN 28 AIR TAWAR TIMUR KOTA PADANG - Ayu Dalfiahri, Tiara; Zainil, Melva (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of fifth-grade students at SD Negeri 28 Air Tawar Timur Kota Padang. This study aims to describe the planning, implementation, and improvement of learning outcomes in measuring the perimeter and area of plane figures using the Indonesian Realistic Mathematics Education approach at SD Negeri 28 Air Tawar Timur Kota Padang. This research is Classroom Action Research (CAR) using qualitative and quantitative approaches, conducted in 2 cycles with procedures consisting of planning, implementation, observation, and reflection. Data collection techniques included observation analysis, tests, and non-tests. The research subjects were the classroom teacher and 28 fifth-grade students at SD Negeri 28 Air Tawar Timur Kota Padang. The results indicate that: First, the teaching module in cycle I obtained an average percentage score of 87 (Good), increasing to 100 (Very Good) in cycle II. Second, learning implementation from the teacher aspect in cycle I achieved 79 (Sufficient), improving to 95 (Very Good) in cycle II. Third, learning implementation from the student aspect in cycle I scored 79 (Sufficient), rising to 95 (Very Good) in cycle II. Fourth, student learning outcomes in cycle I averaged 76.1 (Poor), increasing to 83.6 (Sufficient) in cycle II. Thus, it can be concluded that the Realistic Mathematics Learning (PMRI) approach can improve student learning outcomes in measuring the perimeter and area of plane figures in fifth grade at SD Negeri 28 Air Tawar Timur Kota Padang.